Neurologic Serious Adverse Events Associated with Nivolumab Plus Ipilimumab or Nivolumab Alone in Advanced Melanoma, Including a Case Series of Encephalitis. (11th May 2017) - Larkin, James; Chmielowski, Bartosz; Lao, Christopher D.; Hodi, F. Stephen; Sharfman, William; Weber, Jeffrey; Suijkerbuijk, Karijn P. M.; Azevedo, Sergio; Li, Hewei; Reshef, Daniel; Avila, Alexandre; Reardon, David A.
Abstract : Background: Despite unprecedented efficacy across multiple tumor types, immune checkpoint inhibitor therapy is associated with a unique and wide spectrum of immune‐related adverse events (irAEs), including neurologic events ranging from mild headache to potentially life‐threatening encephalitis. Here, we summarize neurologic irAEs associated with nivolumab and ipilimumab melanoma treatment, present cases of treatment‐related encephalitis, and provide practical guidance on diagnosis and management. Methods: We searched a Global Pharmacovigilance and Epidemiology database for neurologic irAEs reported over an 8‐year period in patients with advanced melanoma receiving nivolumab with or without ipilimumab from 12 studies sponsored by Bristol‐Myers Squibb. Serious neurologic irAEs were reviewed, and relationship to nivolumab or ipilimumab was assigned. Results: In our search of 3, 763 patients, 35 patients (0.93%) presented with 43 serious neurologic irAEs, including neuropathy ( n = 22), noninfective meningitis ( n = 5), encephalitis ( n = 6), neuromuscular disorders ( n = 3), and nonspecific adverse events ( n = 7). Study drug was discontinued ( n = 20), interrupted ( n = 8), or unchanged ( n = 7). Most neurologic irAEs resolved (26/35 patients; 75%). Overall, median time to onset was 45 days (range 1–170) and to resolution was 32 days (2–809+). Median time to onset of encephalitis was 55.5 days (range 18–297); four cases resolved and one was fatal. Conclusion: Both oncologists and neurologists need to be aware of signs and symptoms of serious but uncommon neurologic irAEs associated with checkpoint inhibitors. Prompt diagnosis and management using an established algorithm are critical to minimize serious complications from these neurologic irAEs. Abstract : Melanoma is a particularly immunogenic cancer, and immune checkpoint inhibitors have been extensively studied in this tumor type. This review focuses on the incidence of serious neurologic immune‐related adverse events, specifically encephalitis, in patients with advanced melanoma treated with nivolumab alone or in sequence or combination with ipilimumab. Practical guidance is provided for the diagnosis and management of treatment‐related encephalitis associated with nivolumab and ipilimumab.